Corporate diversification and efficiency: evidence from Taiwanese top 100 manufacturing firms - Wang W.-K.; Ting I.W.K.; Kuo K.-C.; Kweh Q.L.; Lin Y.-H. (Springer Verlag, 2023)
For at least the last two decades, diversification has been an important issue in the strategic management research. This paper explores how diversification affects the corporate performance of the top 100 manufacturing companies in Taiwan, which were selected based on a ranking survey of Taiwanese manufacturing firms conducted by Common Wealth Magazine in 2014. This paper adopts a dynamic data envelopment analysis model to estimate efficiency in the first stage, and adopts OLS regression analysis in the second stage from 2009 to 2013. Two proxies, namely the Entropy approach and the HerfindahlHirschman Index, are used to proxy for diversification. The results indicate that diversification has positive impacts on dynamic efficiency, after controlling firm-specific factors. Concisely, this study empirically proves that diversification is an important corporate strategy for improving corporate performance over long-term periods. Overall, putting eggs in various baskets enable companies to not only survive, but also sustain competitive advantage in todays challenging business world. 2016, Springer-Verlag Berlin Heidelberg.